PENGARUH PENGUNGKAPAN ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DAN GREEN ACCOUNTING TERHADAP RISIKO FINANCIAL DISTRESS - Naila Rif’ah Amelia; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to investigate the effect of Environmental, Social, and Governance (ESG) disclosure practices and green accounting on corporate financial distress. The independent variables in this study consist of environmental disclosure, social disclosure, governance disclosure, and green accounting, while financial distress is used as the dependent variable.The research sample comprises manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sampling technique employed is purposive sampling based on predetermined criteria, resulting in a total of 100 samples. The data analysis method used in this study is multiple linear regression analysis.The results show that environmental disclosure and social disclosure have a negative and significant effect on financial distress. Meanwhile, governance disclosure and green accounting have a positive and significant effect on financial distress.